2019
DOI: 10.1111/avj.12831
|View full text |Cite
|
Sign up to set email alerts
|

Hunting practices in northern Australia and their implication for disease transmission between community dogs and wild dogs

Abstract: Objective This survey aimed to understand hunting practices involving domestic dogs in remote Indigenous communities in northern Australia and, in the context of disease transmission, describe the domestic–wild dog interface and intercommunity interactions of hunting dogs during hunting activities. Methods A cross‐sectional survey of 13 hunters from communities of the Northern Peninsula Area (NPA) of Queensland gathered information on demographics of hunters and hunting dogs, hunting practices and past encount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…This highlights the need for effective movement controls in NPA communities, particularly in the early evening when there is both a greater proportion of dogs that are away from their residence, and those dogs are at greater distances from their residence. Some species such as feral pigs or cats are spill-over hosts for rabies, and whilst it is possible that infected individuals could present some risk (for example to hunters and their dogs 42 ), these populations are unlikely to become a reservoir of canine-rabies and present ongoing risks. However, wildlife canid populations such as red foxes are important hosts of rabies globally, and eradication of rabies in these populations is challenging 43,44 .…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the need for effective movement controls in NPA communities, particularly in the early evening when there is both a greater proportion of dogs that are away from their residence, and those dogs are at greater distances from their residence. Some species such as feral pigs or cats are spill-over hosts for rabies, and whilst it is possible that infected individuals could present some risk (for example to hunters and their dogs 42 ), these populations are unlikely to become a reservoir of canine-rabies and present ongoing risks. However, wildlife canid populations such as red foxes are important hosts of rabies globally, and eradication of rabies in these populations is challenging 43,44 .…”
Section: Discussionmentioning
confidence: 99%
“…Although this was not found to be statistically significant in Dunn's test, a peak of unsupervised domestic dog activity was noticeable in areas that lay further away from the communities towards the tip of the peninsula, which was more pronounced during the wet season compared to the dry season (Figures 2 and 3). This finding is most certainly related to hunting excursions in the bush because these areas were commonly identified by NPA hunters as major hunting areas in a previous survey 11 . The higher level of activity in this area during the wet season is in agreement with the hunter survey, from which hunters reported practicing hunting activities more frequently during the wet season compared to the dry season (median of 12 vs 7.2 hunting trips per season, respectively), although seasonal differences in frequency of hunting trips were not statistically significant (P = 0.09).…”
Section: Figurementioning
confidence: 64%
“…The Northern Peninsula Area (NPA) in northern Queensland, which contains five remote Indigenous communities with an abundant population of free‐roaming domestic dogs, 9 has been identified as a potential rabies incursion point into Australia 8,10 . Together with the recognised roaming behaviour of community dogs in the NPA, 3 hunting activities using domestic dogs are commonly practiced by members of the NPA communities in areas distant from human settlements; during hunting trips, hunters often let their hunting dogs roam freely into the bush unsupervised 11 . A 1‐year camera‐trap study conducted in the NPA revealed the presence of a strong spatial correlation and temporal overlap in daily activities between unsupervised domestic dogs and dingoes, especially during the dry season, suggesting the existence of a wild–domestic interface for potential disease transmission in this equatorial region 12 .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, population parameters were available for Australian models of RABV spread in domestic dogs in the Torres Strait and NPA communities, and dingoes in the NPA. Importantly, thematic maps of the distribution of domestic dogs (and the extent of their roaming), dingoes and the potential sites of interaction between these populations were developed during an intense phase of field research [76][77][78][79][80][81].…”
Section: Disease Modelling: Mitigating Expected Impacts Of Rabv In Australiamentioning
confidence: 99%